2013
DOI: 10.3892/mmr.2013.1721
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-lymphocyte-associated antigen-4 polymorphisms and susceptibility to cervical cancer: A meta-analysis

Abstract: Abstract. Cytotoxic T-lymphocyte associated antigen-4 (CTLA-4) polymorphisms have been examined for associations with cervical cancer in various countries. The results, however, are inconclusive. The present study aimed to explore whether CTLA-4 +49 A/G, -318 C/T and CT60 G/A polymorphisms confer susceptibility to cervical cancer. A meta-analysis was performed with 7,794 subjects included in 15 case-control studies that were published up to January 1, 2013. The results from the meta-analysis indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…In a stratified analysis by ethnicity, a significant association was observed for CTLA-4c.-319*T allele in Asian, but not in Caucasian women. This meta-analysis confirmed the results of the previous studies ( 79 , 80 ). Of note, in study by Pawlak et al ( 73 ) the significant association between CTLA-4c.-319*T allele and G1 grade of tumor was found.…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4supporting
confidence: 91%
See 1 more Smart Citation
“…In a stratified analysis by ethnicity, a significant association was observed for CTLA-4c.-319*T allele in Asian, but not in Caucasian women. This meta-analysis confirmed the results of the previous studies ( 79 , 80 ). Of note, in study by Pawlak et al ( 73 ) the significant association between CTLA-4c.-319*T allele and G1 grade of tumor was found.…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4supporting
confidence: 91%
“…In the study by Xiong et al. (365 women - cases and controls) the carriage of CTLA-4CT60*G allele was associated with increased cervical cancer risk (OR = 1.92), and with more advanced stages of this disease ( 37 ), whereas the other studies did not demonstrate such association ( 73 , 75 , 80 ).…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4mentioning
confidence: 89%
“…h) Can further research confirm whether susceptibility loci in one population are specifically replicated in another e.g. HLA, 4q12, 17q12 (80,116,143,144)? i) Why is the apparent effect of the P72R polymorphism in TP53 gene not consistent in different ethnicities (116)?…”
Section: Iv) What Is Not Known In Host Molecular Genetics Of Cervicalmentioning
confidence: 99%
“… 32 , 33 Certain types of CTLA-4 genetic polymorphism have been proven to be relevant to an increased risk of cervical cancer. 34 , 35 CTLA-4 is expressed on more than 50% of invasive cervical cancer cells and is associated with the clinical stage of the tumor and lymph node metastasis. 36 A clinical trial has found that ipilimumab (anti-CTLA-4) following chemoradiation therapy in locally advanced cervical cancer patients induced an expansion of central and effector memory T cells.…”
Section: Introductionmentioning
confidence: 99%